How to Effectively Reduce Sales Call Reluctance - Kathryn Thornhill; Allen F. Wysocki; Riley Thompson (EDIS)
This document is intended for salespeople who must seek out potential customers, as opposed to waiting for prospects to enter a retail establishment. For these sales professionals, the sales process begins with the salesperson contacting the potential client to schedule an appointment. Types of Call Reluctance, reasons for Call Reluctance, and suggestions for reducing Call Reluctance are presented in this document. This is EDIS document SN011, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published May 2003.